Freezing of the QCD coupling constant and the pion form factor - Aguilar, A. C.; Mihara, A.; Natale, A. A. (World Scientific Publ Co Pte Ltd, 2003)
The possibility that the QCD coupling constant (alpha(s)) has an infrared finite behavior (freezing) has been extensively studied in recent years. We compare phenomenological values of the frozen QCD running coupling between different classes of solutions obtained through non-perturbative Schwinger-Dyson Equations. With these solutions were computed QCD predictions for the asymptotic pion form factor which, in turn, were compared with experiment.